Stop Abusing the Unborn - Abd Razak, Dzulkifli (1995)
THE THOUGHT OF FEEDING BABIES with any substance of dubious origin is really unthinkable. Even in the case of medicines, the general advice is to avoid using them where possible. The intention is of course is to protect the baby from unwarranted injuries. Thus, there is a set of very stringent regulations that must be complied with before a drug could be marketed for use, especially to pregnant mothers. During the Thalidomide tragedy, involving a purported 'safe' drug, many expectant mothers learned a very painful lesson because their babies were exposed to its toxic effects. Unfortunately, when it comes to the use of tobacco and alcohol, despite the welldocumented harmful effects even in adults, such protection is not emphasised. The unborn continue to be exposed to these poisons intentionally or otherwise. This is one form of child abuse that has escaped our attention for too long.